Negotiation: telephonic and email - Kovach, Kimberlee (Henry Stewart Talks, 2013)
Considerations of differences between online and face to face (F2F) negotiations, Importance of communication, Impact of non-verbal communication, Telephonic negotiation, Synchronous and asynchronous communication and negotiation, Preparing for online negotiation, Key stages in negotiation, Styles of negotiation online, Importance of negotiation preparation, Concerns and challenges of online negotiation, Benefits of negotiating online